(untitled) (REMUNOM, 2025)
The Brazilian Anti-Asylum Law represents a pivotal milestone in transforming mental health policy in Brazil, aiming to ensure the dignity, freedom, and social inclusion of individuals with mental disorders. This paper examines the core principles of Law No. 10.216/2001 and its contribution to the advancement of human rights, highlighting both the progress achieved and the ongoing challenges in its implementation. It discusses the strategic role of the Psychiatric Reform in promoting community-based and humanized models of care, in contrast to the historically exclusionary asylum model. The study also underscores the importance of respecting users’ autonomy and citizenship as essential conditions for overcoming stigma and social marginalization. It concludes that the full realization of the Anti-Asylum Law depends on the continued commitment of the State, civil society, and public institutions to developing effective public policies and upholding the fundamental rights of individuals experiencing psychological distress.